Analysis of Raindrop Diameters for Rainfall Attenuation in Southern Africa - Oluwumi Adetan; Obiseye Obiyemi (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The influence of critical raindrop diameters on the specific rainfall attenuation in Durban (29o52'S, 30o58'E), South Africa using various rainfall regimes is analyzed in this paper. Different rain rate values representing drizzle, widespread, shower and thunderstorm are selected for the purpose of analysis over the measured raindrop size distribution. The three-parameter lognormal and gamma DSD models with shape parameter of 2 are used to estimate the parameters required to investigate the drop sizes which produce a major contribution to the total specific rainfall attenuation for the selected rain rate values. The computed total specific attenuation increases with increasing frequencies and rain rates. The highest and prevailing contribution to the specific attenuation occurs at  for the stratiform (drizzle or widespread) and convective (shower or thunderstorm) rain types for the models considered.  The total percentage fraction formed by drops in the diameter range 0.5 mm ≤ D ≤ 2.5 mm and 1.0 mm ≤ D ≤ 3.0 mm are found to be most critical for the specific rain attenuation for the stratiform (drizzle and widespread)  and convective (shower and thunderstorm) rainfall types especially at higher frequencies.